"Youth is not a political position": Exploring justice claims-making in the UN Climate Change Negotiations. (March 2020) - Thew, Harriet; Middlemiss, Lucie; Paavola, Jouni
Highlights: Youth switch from intergenerational to intragenerational climate justice claims. Participation justice theory must consider procedural and representation justice. Self and social recognition matter for the articulation of justice claims. Ideological power shapes justice claims-making in environmental governance. Abstract: Youth articulations of climate change injustice are experiencing an unprecedented moment in the spotlight as, inspired by Greta Thunberg, young people around the world take to the streets demanding justice for their generation in the face of climate emergency. Formal opportunities for youth voices to be heard in environmental governance are slim, although the UN Framework Convention on Climate Change (UNFCCC) offers a rare opportunity for youth to share their perspectives as one of nine civil society constituencies: YOUNGO. Recent research in Global Environmental Change has called for empirical exploration of justice claims-making by different stakeholders to develop understanding of how justice is conceptualised and negotiated in climate change governance spaces. To date, climate justice claims from youth have not been explored in the academic literature. This paper draws upon rich, ethnographic, longitudinal data on the evolution of justice claims made by a group of youth participants in the UNFCCC to contribute to this empirical gap. In our research, a UK-based case study organisation and long-established member of YOUNGO was studied between 2015 and 2018, including observation of their participation at the 21st, 22nd and 23rd Conferences of the Parties. We find that youth participants first articulated injustices based on perceived future risks to their generation but, over time, switched to solidarity claims about injustices experienced by other groups in the present. Whilst laudable, this impedes their mandate as representatives of younger generations. We also make three theoretical contributions to environmental justice theory. First we expand participation justice theory to both the visible structures of participation ( procedural justice ) and the informal rules and discourses shaping participation ( representation justice ). Second we demonstrate the importance of both external and self-recognition for the articulation of justice claims. Third we clarify the relationship between power and justice claim-making, proposing that we must look beneath what is articulated to shed light on the exercise of ideological power that shapes the framing and claiming of justice in environmental governance spaces.